PROPHYLAXIS AND MANAGEMENT OF CHEMOTHERAPY-INDUCED FEBRILE NEUTROPENIA: THE ROLE OF MYELOID GROWTH FACTORS - Dimitrijevic, Jelena; Stojanovic, Marko (Medicinski podmladak, 2022)
Febrile neutropenia is a serious chemotherapy-related adverse event that can lead to complications and death and it could be a burden to the health care system. The risk for febrile neutropenia is determined by chemotherapy myelosuppressivity and the presence of patient-related risk factors. Various patient-related factors are taken into consideration, among which the patient age is the most important. If the estimated risk for the febrile neutropenia is high, prophylactic use of myeloid growth factors (granulocyte colony-stimulating factor and granulocyte-macrophage colony-stimulating factor) is recommended. In patients with solid tumors and lymphomas it was shown that the prophylactic use of myeloid growth factors significantly reduces the incidence of febrile neutropenia, early mortality during chemotherapy and infection-induced mortality. In patients presenting with febrile neutropenia, there is less evidence for the therapeutic use of myeloid growth factors compared to prophylactic use, although there is a clear benefit in reducing the time to neutrophil recovery and duration of hospitalization. In patients presenting with febrile neutropenia who have not been previously treated with prophylactic myeloid factors, assessment of risk factors for the poor outcome is advised. In patients with high-risk febrile neutropenia therapeutic use of growth should be considered.